2023
DOI: 10.3389/fbioe.2023.1199604
|View full text |Cite
|
Sign up to set email alerts
|

PPGFeat: a novel MATLAB toolbox for extracting PPG fiducial points

Abstract: Photoplethysmography is a non-invasive technique used for measuring several vital signs and for the identification of individuals with an increased disease risk. Its principle of work is based on detecting changes in blood volume in the microvasculature of the skin through the absorption of light. The extraction of relevant features from the photoplethysmography signal for estimating certain physiological parameters is a challenging task, where various feature extraction methods have been proposed in the liter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…Two databases were used to validate the pyPPG toolbox (see table 2 ). The multi-ethnic study of atherosclerosis (MESA) database (Dean et al 2016 , Zhang et al 2018 ) was used to validate the peak detector, and the PPG and blood pressure (PPG-BP) database (Liang et al 2018 , Abdullah et al 2023 ) was used to validate the fiducial point detection algorithm. The MESA database consists of polysomnography (PSG) recordings from 2056 adults, aged 54–95 years, with subclinical cardiovascular disease, including 19 998 h of PPG recordings (Chen et al 2015 , Rinkevičius et al 2023 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two databases were used to validate the pyPPG toolbox (see table 2 ). The multi-ethnic study of atherosclerosis (MESA) database (Dean et al 2016 , Zhang et al 2018 ) was used to validate the peak detector, and the PPG and blood pressure (PPG-BP) database (Liang et al 2018 , Abdullah et al 2023 ) was used to validate the fiducial point detection algorithm. The MESA database consists of polysomnography (PSG) recordings from 2056 adults, aged 54–95 years, with subclinical cardiovascular disease, including 19 998 h of PPG recordings (Chen et al 2015 , Rinkevičius et al 2023 ).…”
Section: Methodsmentioning
confidence: 99%
“…The human heart rate ranges between 30 and 200 beats per minute (Paliakaitė et al 2020 ). Therefore, in PPG signal analysis, it is common to apply bandpass filtering such 0.5−8 Hz (Abdullah et al 2023 ), 0.5−10 Hz (Finnegan et al 2023 ), 0.5−15 Hz (Mejia-Mejia et al 2022 ), 0.5−20 Hz (Allen and Murray 2000 , Liang et al 2018 ), or 0.5−25 Hz (Chowdhury et al 2020 ), to conserve the frequency content of the PPG pulse waves while filtering out lower-frequency content (e.g. baseline wander due to respiration) and higher-frequency content (e.g.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we aim to develop a ML-based approach for estimating four different hypertension stages: (normal, prehypertension stage, stage 1 hypertension, stage 2 hypertension), using 19 features derived from statistical analysis of the APG waveform and the clinical parameters age, heart rate and systolic blood pressure. The features were extracted using the fiducial point extraction algorithms explained in our recently released MATLAB toolbox, PPGFeat ( 18 ).…”
Section: Methodsmentioning
confidence: 99%
“…Numerous studies have demonstrated that the amplitude and timing of these points can provide valuable information about the aging process and support the assessment of cardiovascular disease ( 11 , 13 17 ). The identification of the c and d points, however, is not trivial since they can be undetectable or non-prominent in the APG waveform ( 18 , 19 ).…”
Section: Introductionmentioning
confidence: 99%